A numerical assessment on water quality model using the half-sweep explicit group methods / M. H. Abdullah, J. Sulaiman and A. Othman - Abdullah, M. H.; Sulaiman, J.; Othman, A. (Universiti Teknologi MARA Cawangan Pahang, 2006)
Presently, there are many. science and engineering problems described in mathematical models. The solutions to these problems can be obtained analytically or numerically. Thus, the aim of this paper is to assess the water quality model using full- and half-sweep finite-difference approximation equations. The 2, 3 and 4-point of Full-Sweep Explicit Group (FSEG) and Half-Sweep Explicit Group (HSEG) iterative methods together with the Red-Black (RB) ordering strategy were also presented to solve the systems of linear equations. Finally, a number of numerical experiments were conducted in order to show the effectiveness of the HSEG methods with RB ordering in computing numerically.